The Determination of Metals and Minerals Contains in The Water of Pucung River, Prehistoric Site Sangiran, Central of Java - Agung Rimayanto Gintu; Cucun Alep Riyanto; Widhi Handayani; Andri Purnomo; Stefanus Agung Wicaksono (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
Sangiran was an important prehistoric site heritage for Indonesia. Entire site area was living environment once pass by several rivers, one of them was Pucung river. This study was approaching study from water environment by measuring metals and minerals contained in the water from Pucung river and measured that Iron (Fe) containend was 0,01mg/L; Zink (Zn) 0,02mg/L; Nickel (Ni) 0,00mg/L; Mangan (Mn) 0,00mg/L; Chrom (VI) (Cr6+) 0,009mg/L; Aluminium (III) (Al3+) 0,00mg/L and Copper (Cu) 0,01mg/L. From the minerals containing measured that Phosphate (PO4) 0,37mg/L; Nitrate (NO3-) 0,8mg/L; Nitrite (NO2-) 0,001mg/L; Chloride (Cl-) 0,01mg/L; Fluoride (F-) 0,00mg/L; Sulphide (S2-) 0,0µg/L; Sulphate (SO42-) 6,00mg/L; and N as N-NH3 (Ammonia) 0,05mg/L. This studi continuing the study before wich are just limiting to studying the river stratigraphy..